Bioengineering Applications of Carbon Nanostructures - Jorio, Ado.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book covers the development of biotechnology based on carbon nanostructures, with a focus on nanotubes, addressing also fullerenes and amorphous carbons. The book is divided into 7 chapters, addressing tissue engineering, genetic engineering and therapy, as well as the environmental and health impacts of carbon nanostructures. .
Keywords: Biomaterials; Biomedical engineering; Nanotechnology; Biomaterials; Biomedical Engineering and Bioengineering; Nanotechnology